Increase in distance of freight traffic as the long-term economic trend - D. A. Macheret (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
The analysis of average distance of freight transportation of the largest railway systems of the world made in article - domestic and North American allows making the conclusion that increase of average distance of transportations has long-term character and is caused by the fundamental factors connected with regularities of economic growth. At the same time it is revealed that annual average rate of a surplus of average distance of freight transportation for both considered railway systems is very close and constitutes about 1 %. Growth of distance of transportations happened both in market conditions and in case of centralized state planned economy, during domination of a rail transport in freight transportation and in the conditions of active shift of part of freight flows to other transport modes (first of all pipeline and automobile). The new indicator is offered - “average distance of general movement of goods” which, unlike distance of transportation by a specific transport mode, will characterize movement of goods from the producer to the final consumer within a global exchange, end-to-end logistics of merchandising. The conclusion is drawn on that due to the goods delivery on a long distance effective interregional job specialization is provided, as well as specialization and cooperation of production, local monopolies are undermined and as a result efficiency of economy and welfare of people increases. At the same time in the conditions of considerable range of transportations technical and economic advantages reveal and high competitiveness of the railroads is provided.